Americas the changing face of Latin America and the Caribbean. - Winn, Peter (New York Pantheon Books, 1993)
Discusses "similarities and differences among the thirty-three countries."
Php 400.00.
Includes bibliographical references (pages 601-612) and index
Donated by Ma. Luisa Mabunay Ph. D.
Keywords: Latin America -- History -- 20th century; Caribbean Area -- History -- 1810-1945.; Caribbean Area -- History -- 1945-